Semantic change of pronominal adverbs for «so»: models and motivation - Yermolenko, S.S. (Мовознавство, 2016)
In this article, the analysis of the secondary meanings of adverbs for «so» in selected Indo-European languages has established peculiar features of the semantic change of such items, linking these features to the semiotic nature of demonstratives as indexical signs equivalent to the pointing gesture used in the prototypical cognitive-communicative situation.